2008
DOI: 10.1007/978-3-540-69534-9_39
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Method Engineering: An Analysis of Existing Environments

Abstract: Analogous to Computer-Aided Software Engineering (CASE), which aims to facilitate Software Engineering through specialized tools, Computer-Aided Method Engineering (CAME) strives to support a wide range of activities carried out by method engineers. Although there is consensus on the importance of tool support in method engineering, existing CAME environments are incomplete prototypes, each covering just a few steps of the method engineering process. This paper summarizes the history and the state of the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…For example, scale 2 was wholly added to fit the evaluation of the coverage criterion. We have also selected and adapted certain general evaluation criteria, such as usability, from [7], which provides an analytical review of Computer Aided Method Engineering (CAME) tools. During the criteria definition and refinement process, we have strived to keep the criteria general, precise, comprehensive and balanced in order to satisfy the metacriteria of [34].…”
Section: H Evaluation Of the Selected Pseesmentioning
confidence: 99%
“…For example, scale 2 was wholly added to fit the evaluation of the coverage criterion. We have also selected and adapted certain general evaluation criteria, such as usability, from [7], which provides an analytical review of Computer Aided Method Engineering (CAME) tools. During the criteria definition and refinement process, we have strived to keep the criteria general, precise, comprehensive and balanced in order to satisfy the metacriteria of [34].…”
Section: H Evaluation Of the Selected Pseesmentioning
confidence: 99%
“…Regardless of the potential benefits of ME and the emergence of ComputerAided Method Engineering (CAME) technology [8], ME has never been widely used in industry [9,10]. Kuhrmann et al concluded in a recent mapping study [11] that there are hardly any reports on the practical application of ME available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the Method Engineering literature, we can find lifecycle models of different nature [41,59,60]; nonetheless, all these models comprise generic phases that are similar to those proposed by the Software Engineering community. These phases are graphically depicted in Figure 2.3.…”
Section: Defining Methods Engineeringmentioning
confidence: 99%
“…However, despite the great achievements of existing CAME environments (e.g., the design of the product part of methods is fully supported by a wide variety of metamodeling notations [41]), these tools still present important deficiencies: incomplete support to the Method Engineering lifecycle, weak process support, and high complexity; furthermore, these tools are affected by the negative perception of practitioners with respect to the usefulness of Method Engineering. We argue that all of these problems are the key determinants of the little use of Method Engineering in industrial contexts.…”
Section: Research Motivationmentioning
confidence: 99%
See 1 more Smart Citation